IMPELEMENTASI KEGIATAN EKSTRAKULIKULER PRAMUKA DALAM MEMBENTUK KARAKTER DISIPLIN SISWA DI MI AL-FATTAH MALANG - Suhartini Koti; Devi Wahyu Ertanti; Mutiara Sari Dewi (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Discipline is the attitude that everyone has within themselves. Therefore, there should be a companion the activities to achieve it. Dicipline attitude is very important to the development of students in this age.Character is very important influence in student discipline. Scout extracuriculer activities are also very influential in increasing the caracter of student discipline. That is reasonably necessary, given the scout are out of school education helps governments. This is seen by the existence of a number of scout extracurricular activities which can support the disciplinary character of student as foolows. There are various activities available in MI AL-FATTAH that can support the caracter of disipline; nature exploring, camping, marching lines, routine training and SEJ (scout east java) and in imlementing the discilplinay character, there are 6 indikator as follows disciline face temptetion and sho forth Key word: Disciplined character and scout